Development of Downtown Open Space to Mitigate Urban Heat Island Effect: A Case Study of Silom Road, Bangkok - Saiyavath, Puntipha; Haocharoen, Kritaporn (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This research concerns the development of downtown open space to reduce the effect of urban heat island (UHI) phenomenon. Research papers about open space development and UHI problem solution were studied to be used as an analysis with a site survey. Due to the open space survey, the characteristics of the open space that can reduce heat in downtown should be a useful open space that brings natural environment into downtown for pleasure and relaxation. Although this land usage cannot enhance economic benefits, it can provide social fields. Not only the characteristic of the natural environment, but also that of the physical component that the open space should take into account of consequently, the development of open space for the most advantage, will turn to be public parks and vertical gardens.